2022
DOI: 10.3390/fintech1040027
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Port Users’ Behavioral Intentions to Adopt Financial Technology (Fintech) in Ports in Sub-Saharan Africa: A Case of Ports in Ghana

Abstract: The study evaluated factors influencing port users’ intentions to participate in Financial Technology (Fintech) in the ports of Ghana. The study used non-experimental quantitative correlational design and the Extended Unified Theory of the Acceptance and Use of Technology (UTAUT2) as the theoretical foundation to assess whether performance expectancy (PE), behavioral intention (BI), effort expectancy (EE), social influence (SI), facilitating conditions (FC), hedonic motivation (HM), price value (PV), and habit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 71 publications
(128 reference statements)
0
6
0
Order By: Relevance
“…This approach aimed to increase variety in the sample population, hence improving the representativeness and validity of the findings. To address this gap between theoretical motivations and practical intentions, a tailored quantitative analysis was performed, in particular, a quantitative non-experimental correlation design adapted from [64,65]. An explicit self-administrated web survey was conducted through particular sites typically used by potential and existing blood donors.…”
Section: Methodology and Measurementsmentioning
confidence: 99%
“…This approach aimed to increase variety in the sample population, hence improving the representativeness and validity of the findings. To address this gap between theoretical motivations and practical intentions, a tailored quantitative analysis was performed, in particular, a quantitative non-experimental correlation design adapted from [64,65]. An explicit self-administrated web survey was conducted through particular sites typically used by potential and existing blood donors.…”
Section: Methodology and Measurementsmentioning
confidence: 99%
“…In the case of financial technology adoption, if consumers perceive that appropriate guidance and the required support are available, then they will be motivated to adopt Fintech services. Conversely, Antwi-Boampong et al [ 26 ] found no impact of facilitating factors on UI, indicating mixed findings on the impact of promoting conditions on FUI. As behaviour can be predicted with known behavioural control, future studies could develop the analysis of the impact of facilitating conditions on FUI.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…That is, when users find the technology to be relevant to or addresses their needs, they will accept it. Consistent with the relevant theories, several studies have established behavioural intention as an outcome variable in examining the relationship between behavioural intention and social and facilitating factors [ 24 , 26 , 36 ]. Furthermore, according to the UTAUT2 model, sociodemographic variables such as age, income and experience have been hypothesised to moderate the effect of fintech on behavioural intention [ 20 ].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Daragmeh et al (2021), a definition of BI is the probability that a person would engage in a particular behavior. According to Antwi-Boampong et al (2022), BI are cognitive drivers that evaluate the number of struggle a person is willing to put in to carry out a behavior.…”
Section: Literature Reviewmentioning
confidence: 99%